Efficacy of lenvatinib combined with TAS-102 as second-line therapy for advanced intrahepatic cholangiocarcinoma: a case report - Li, Hailong; Liu, Zhiqiang; Zhang, Mei (Frontiers in Oncology, 2025)
Currently, chemotherapy remains the primary treatment modality for advanced intrahepatic cholangiocarcinoma (iCCA). However, the efficacy of existing regimens in patients requiring later-line therapy is limited, with low objective response rates and considerable adverse effects. Therefore, the development of effective and safe novel therapeutic strategies is of critical importance. We report a case of unresectable metastatic iCCA in which first-line therapy with a PD-1 inhibitor combined with a tyrosine kinase inhibitor (TKI) failed. The patient subsequently received second-line treatment with lenvatinib in combination with trifluridine/tipiracil (TAS-102), which resulted in significant tumor shrinkage and a partial response (PR) upon evaluation, without the occurrence of grade 3 or higher adverse events. The progression-free survival (PFS) was 13.33 months. This case suggests that lenvatinib combined with TAS-102 may demonstrate favorable antitumor activity and may represent a promising therapeutic option for advanced iCCA in the later-line setting.